2020
DOI: 10.4236/ojas.2020.102016
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Polymorphism of Pituitary Specific Transcription Factor 1 Gene and Its Association with Bodyweight of Fulani and Yoruba Ecotype Chickens

Abstract: Pituitary Specific transcription factor 1 (PIT-1) gene is one of the POU gene family and play key roles in the regulation of muscle development which is important for body weight in chickens. This study was carried out to detect the polymorphism of PIT-1 gene and study its association with body weight in Fulani and Yoruba ecotype of Nigerian indigenous chickens. A total of 100 day-old chicks comprising of fifty chicks of Fulani and Yoruba ecotypes were used for this study. These chicks were genotyped using PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Hence, these polymorphisms of prolactin as candidate gene could serve as useful physiological markers, to increase egg production in the Nigerian chicken population. In the same vein, Bello et al (2020) reported that the Pituitary Specific transcription factor 1 (PIT-1) gene evaluated in their study was polymorphic with genotypes AA and AB in the Fulani and Yoruba ecotypes of the NIC studied. According to these authors, the PIT-1 genes were statistically associated with the chickens' body weight.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…Hence, these polymorphisms of prolactin as candidate gene could serve as useful physiological markers, to increase egg production in the Nigerian chicken population. In the same vein, Bello et al (2020) reported that the Pituitary Specific transcription factor 1 (PIT-1) gene evaluated in their study was polymorphic with genotypes AA and AB in the Fulani and Yoruba ecotypes of the NIC studied. According to these authors, the PIT-1 genes were statistically associated with the chickens' body weight.…”
Section: Methodsmentioning
confidence: 80%
“…However, to the best of our knowledge, this is the first work on SNP approach to the study of the Nigerian indigenous chicken prolactin gene and its association with Light Ecotype chicken's egg traits. Notwithstanding, association studies have been done on morphometric and growth traits in some breeds of the Nigerian chicken, including the indigenous birds (Okafor et al 2019;Bello et al 2020). In a recent study of Okafor et al (2019) the chicken growth hormone SNP was associated with morphometric and growth traits in the NIC in addition to Funaab Alpha and ShikaBrown.…”
Section: Methodsmentioning
confidence: 99%
“…Modeling of components of gene-associated selection opens rather wide perspectives and is actively used in selection programs of different countries with indigenous and local populations/breeds of chickens. A good illustration for the above mentioned may be found in the studies on polymorphism of genes, whose products are involved in the network of humoral regulation, and whose allelic variants are potentially associated with the manifestation of economic traits (Esmailnejad et al, 2018;Ahmadi et al, 2019;Bello et al, 2020).…”
Section: Introductionmentioning
confidence: 99%